Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan di Unit Usaha Retail Kobantitar Mart - Putri, Aldila Rahma (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
In today’s competitive retail landscape, customer satisfaction has become a crucial factor for business sustainability. Service quality plays a central role in shaping customer experiences and influencing their loyalty. This study investigates the impact of service quality on customer satisfaction at Kobantitar Mart, a retail outlet striving to enhance its service standards to meet growing consumer expectations. The research employs a descriptive analysis method with a quantitative approach, utilizing a series of statistical tests to ensure data validity and reliability. The findings reveal that service quality has a positive and significant impact on customer satisfaction both partially and simultaneously. When the quality of service improves, customer satisfaction tends to increase. Conversely, a decline in service standards leads to reduced customer satisfaction. These results highlight the essential role of consistent and high-quality service delivery in fostering customer loyalty and ensuring business success. Furthermore, the study indicates that while service quality contributes substantially to customer satisfaction, there are still other influential factors outside the scope of this research. These insights suggest that continuous investment in service improvement is vital for maintaining competitive advantage and customer retention.